EFFICACY OF COLISTIN AND NON-COLISTIN MONOTHERAPIES IN MULTI-DRUG RESISTANT ACINETOBACTER BAUMANNII BACTEREMIA/SEPSIS - (:unkn) unknown (CARBONE EDITORE, 2014)
Objective: This retrospective study aimed to investigate the efficacies of colistin and non-colistin monotherapies in multi-drug resistant Acinetobacter baumannii bacteremia (MDR-AB). Materials and methods: Cases with MDR-AB from 27 tertiary-referral hospitals between January 2009 and December 2012 were included. Patients' data that were on either colistin monotherapy (CM) or non-colistin monotherapy (NCM) were compared. Mortality on Day 14 was the primary endpoint, whereas microbiological eradication and clinical outcome were the secondary ones. Results: Eighty-four cases were included in the study with 36 being in the CM group and 48 in the NCM group. Thirty-eight (452%) cases were male and the mean age was 602 years. The mean durations of pre-MDR-AB hospital stay and intensive care unit stay were 25.8 days and 20.9 days, respectively. All of the cases had fever (>38 degrees C). The mean Pitt bacteremia score (PBS) of the patients was calculated as 6.8, APACHE 2 score as 18.9 and the Charlson co-morbidity index (CCI) as 3.7 (CM: 3.6 vs. NCM: 3.9). Twenty (55.6%) cases in the CM group and 26 cases in the NCM group (542%) (p=0.81) died; 9 cases in the CM group (25%) and 16 cases in the NCM group (33 3%) had treatment failure (P=0.55). Bacteriological eradication was achieved in 20 (55.6%) cases in the CM group and in 36 cases (75%) in the NCM group (P=0.061). Conclusions: No significant difference could be identified between the colistin monotherapy and non-colistin monotherapy options in MDR-AB cases with respect to the results of efficacy and 14-day mortality.
Keywords: Acinetobacter baumannii; bacteremia; colistin; monotherapy; multi-drug resistant; sepsis; COMBINATION THERAPY; CLINICAL IMPACT; RISK-FACTORS; INFECTIONS; AMPICILLIN; SULBACTAM; EMERGENCE; VS.